Self-monitoring of blood glucose - an effective measure to prevent cardiovascular disease in patients with diabetes - EV Biryukova (Медицинский совет, 2014)
The global increase in the prevalence of diabetes mellitus (DM) is a serious public health problem. DM is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both (WHO, 1999). Currently, there are 382 million people with diabetes worldwide; forecasts are disappointing: by 2035, the figure will exceed 592 million [8]. The vast majority are patients with type 2 diabetes (DM 2). According to the State Register, in Russia (2013), the number of diabetic patients was 3 million 770 thousand, of whom 3.5 million had DM 2 [1].